Untargeted Metabolomics Reveals the Protective Effect of Fufang Zhenshu Tiaozhi (FTZ) on Aging-Induced Osteoporosis in Mice - Luo, Duosheng; Li, Jingbiao; Chen, Kechun; Rong, Xianglu; Guo, Jiao (Frontiers in Pharmacology, 2019)
Fufang Zhenzhu Tiao Zhi (FTZ) is an effectively traditional Chinese medicine has been prescribed for 20 years, which has been issued patent and clinically proven for use in the treatment of dyslipidemia, glucocorticoid-induced and high - fat - induced osteoporosis, but its effect on osteoporosis induced by aging is unclear. The study is to investigate the anti-osteoporosis effect of FTZ in aging mice and its mechanism using UPLC-TOF/MS. Method: Establish model of primary osteoporosis induce by aging, 12 female C57BL/6J Narl mice 21 months old was divided into two groups: model group and treatment group,the other 6 female C57BL/6J Narl mice 4 months old represent control group. The treatment mice were orally administered FTZ extract at a therapeutic dose (1.0 g/kg, expressed as the weight of raw material) once daily during the experient, control group and model group were orally gavaged approximately volume normal saline solution. After 12 weeks, all plasma samples of three groups were collected and their metabolic changes were analyzed by ultra-performance liquid chromatography-tandem mass spectrometry (UPLC–MS/MS). The resulting dataset was analyzed using principal component analysis (PCA) and partial least squares discriminant analysis (PLS-DA), clinical biomechanics and biochemistry study were also carried out to prove the success of the osteoporosis model induced by normal ageing and to evaluation the anti-osteoporosis effect of FTZ. Results: The changes of histomorphometric and biomechanics of femurs, osteoblast and osteoclast activity indicated that FTZ could improve the risk of osteoporosis. Metabolomics results showed that clear separation trend between control and model group was found in PCA score plot, the anti-osteoporosis effect of FTZ can be displayed in PLS-DA score plot, sphingosine 1-phosphate, LPA (0:0/16:0), arachidonic acid and so on were the key biomarkers. Pathway analysis reveal the pivotal pathways included sphingolipid metabolism, glycerophosphoipid metabolism and arachidonic acid metabolism. The mechanism of FTZ on primary osteoporosis mice induce by aging might relate to disorders of above-mentioned pathways. Conclusion: FTZ have the effect of anti-osteoporosis induce by ageing and its mechanism might be via intervening Sphingolipid metabolism, Glycerophosphoipid metabolism and arachidonic acid metabolism in vivo in mice.